Status of the IRAM observatories - Neri Roberto; Sánchez-Portal Miguel (EPJ Web of Conferences, 2022)
The NOEMA interferometer and the IRAM 30-meter telescope offer a range of outstanding capabilities that will continue to be expanded as part of IRAM’s long-term development strategy.